The Digital Division of Labor: Socially Constructed Design Patterns of Amazon Mechanical Turk and the Governing of Human Computation Labor - Ellmer, Markus (Momentum Quarterly, 2015)
From a Social Construction of Technology (SCOT) perspective, this article provides a critical analysis of Amazon Mechanical Turk (AMT), currently one of the major distribution systems in Human Computation labor markets. Drawing from classical Labor Process Theory, AMT’s infrastructure, shaped by discourses on digital labor, determines critical power and information asymmetries in favor of employers (Requesters) and enables a specific mode of digital labor division. Its effects (deskilling, pricing, efficiency enhancement) are enhanced by a crowdsourcing-based access to highly fragmented digital workers (Turkers). The SCOT approach uncovers the social construction of digital labor division and hierarchies by means of different qualities of influence on infrastructure and labor process design issues. These capacities depend on different actor-related capacities to enforce and implement meanings and interpretations on the technological artifact. Turkopticon, a browser-extension, mitigates these produced hierarchies by adding a Requester rating system directly on AMT’s interface.
Keywords: Amazon Mechanical Turk; human computation; Turkopticon; digital labor; social shaping of technology; social construction of technology